The other face of the crisis: the importance of sanitation sector in the context of water scarcity - Leao, Renata de Souza; Arteiro da Paz, Mariana Gutierres [UNESP]; Cibim, Juliana Cassano (Assoc Servidores Arquivo Nacional, 2016)
Have received attention and have been in international global agenda. Recently, the discussion about water availability has been more frequent due to the lack of water in some regions of the State of Sao Paulo. Water scarcity is a dynamic concept and includes some aspects such as water quantity and quality. The sanitation sector is one water user which can interfere in water quantity and water quality as well. This happens because domestic effluent discharges are the main source of water pollution in urban areas in Brazil. This article aims to discuss water scarcity by sanitation services perspective. Also, it intends to promote the discussion about integrating water and sanitation policies towards sustainable water use.
Keywords: Water scarcity; sanitation services; policy integration